2005
DOI: 10.1111/j.1420-9101.2004.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation or exaptation? An experimental test of hypotheses on the origin of salinity tolerance inBufo calamita

Abstract: The natterjack toad (Bufo calamita) shows variation in embryonic and larval salinity tolerance across populations in southern Spain. However, its aquatic/terrestrial biphasic life cycle, together with remarkable differences in salinity tolerance between Spanish and UK freshwater populations suggest an alternative hypothesis to local adaptation. Drought resistance during the terrestrial phase and salinity tolerance during the aquatic phase are both related to osmotic stress tolerance, and if there were an assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…In southeast Spain, populations of the water frog, Pelophylax perezi, from aquatic environments with high levels of nitrogen pollution showed higher survival and larger final size than populations from less polluted environments (Egea-Serrano et al 2009). Such observations can be explained by variations between populations' genetic tolerance to environmental stressors (Semlitsch et al 2000;Gomez-Mestre and Tejedo 2005;Marquis et al 2009). …”
Section: Introductionmentioning
confidence: 95%
“…In southeast Spain, populations of the water frog, Pelophylax perezi, from aquatic environments with high levels of nitrogen pollution showed higher survival and larger final size than populations from less polluted environments (Egea-Serrano et al 2009). Such observations can be explained by variations between populations' genetic tolerance to environmental stressors (Semlitsch et al 2000;Gomez-Mestre and Tejedo 2005;Marquis et al 2009). …”
Section: Introductionmentioning
confidence: 95%
“…Drier substrates decrease postmetamorphic growth rate, enhance burying behavior and decrease foraging activity and efficiency in B. calamita (Gomez-Mestre and Tejedo, 2005). Likewise, field reciprocal transplant experiments on P. cultripes juveniles between sandy and granite-schist soil environments show reduced growth in the sandy environment (Tejedo and Marangoni, unpublished data).…”
Section: Growing On Sandy Soilsmentioning
confidence: 96%
“…In support of this idea, some authors have found a positive correlation between body size and aridity in some frog species (Nevo, 1973;Rosso et al, 2004). Alternatively, by imposing high energetic costs of maintaining water balance, sandy substrates may constrain growth by reducing activity or foraging efficiency (Rohr and Madison, 2003;Gomez-Mestre and Tejedo, 2005) or, indirectly, by limiting availability of food resources (Rohr, 1997;Bronikowski and Arnold, 1999;Tracy, 1999). The observed dwarfism associated to sandy soils in Doñana contradicts the expected morpho-functional advantage of large size in desiccating substrates and therefore seems to be nonadaptive.…”
Section: Growing On Sandy Soilsmentioning
confidence: 96%
“…It is possible, however, that salamanders in dry treatments spent an equal time out of the burrow but chose not to feed. Gomez-Mestre and Tejedo [81] found that Bufo calamita in dry environments were also less efficient at catching prey. The prey in our experiment was confined to a small container, so we assume that salamanders in both low and high moisture treatments were equally efficient at catching the prey.…”
Section: Discussionmentioning
confidence: 99%